SDGs DISCLOSURES IN SUSTAINABILITY AND ANNUALREPORTS IN INDONESIA - Nugraha, Farhani; Mustofa, Muhamad; Mudhakir, Diki; Innasarah; Sasongko, Ananta (Jurnal Magister Akuntansi Trisakti, 2025)
This study investigates the extent of disclosure of sustainable development goals (SDGs) in the sustainability and annual reports of Indonesia's ten largest companies by market capitalization from 2016 to 2023. Through content analysis, the findings indicate that SDG reporting remains relatively limited, with companies exhibiting significant variations in the depth and quality of their disclosures. While some firms integrate SDGs into their corporate strategies and sustainability initiatives, others provide minimal references without clear implementation frameworks. This variation suggests that regulatory requirements and voluntary corporate commitments are crucial in shaping disclosure practices. The study underscores the necessity of stronger regulatory frameworks and heightened corporate engagement to ensure alignment with global sustainability objectives. By addressing existing gaps in SDG disclosure research in Indonesia, this paper contributes to the academic literature on sustainability reporting. Additionally, it provides practical insights for policymakers, regulators, and business leaders to enhance corporate transparency, accountability, and long-term commitment to sustainable development initiatives.